Multimodal imaging of optic nerve head abnormalities in high myopia - Hu, Ruihan; Wu, Qiuyan; Yi, Zuohuizi; Chen, Changzheng (Frontiers in Neurology, 2024)
Highly myopic optic nerve head (ONH) abnormalities encompass a series of complications resulting from the stretching of papillary and peripapillary structures during significant axial elongation. The morphological changes in the ONH typically initiate with disc tilting or rotation, progressing to PHOMS and PPA. Tissue defects in each layer manifest as focal lamina cribrosa defects (FLDs), peripapillary intrachoroidal cavitations (PICC), and acquired pits of the optic nerve (APON). Anterior vitreous/vascular traction and posterior scleral protrusion may lead to prelaminar schisis as well as paravascular cysts and holes, which can potentially develop into retinoschisis. Traditional color fundus photography(CFP) is often insufficient for visualizing most of these lesions, yet their description and quantification benefit significantly from the advancements in optical coherence tomography (OCT) and OCT angiography (OCTA), complemented by fundus autofluorescence (FAF), indocyanine green angiography (ICGA), and three-dimensional imaging. The effective diagnosis and classification of ONH abnormalities heavily rely on a comprehensive understanding of their multimodal imaging features outlined in this review. These findings provide valuable insights into optic neuropathy in high myopia, establishing a solid foundation for future endeavors in disease monitoring and treatment guidance.